Viral and bacterial infection in acute asthma and chronic obstructive pulmonary disease increases the risk of readmission. Issue 6 (25th July 2013) - Wark, Peter A.B.; Tooze, Melinda; Powell, Heather; Parsons, Kristy
Abstract: Background and objective: Infection is as an important trigger for acute asthma and chronic obstructive pulmonary disease (COPD). The aim of this article was to determine the prevalence and impact of virus and bacterial infections in acute asthma and COPD. Methods: Subjects were recruited, within 24 h of hospital admission for acute exacerbations of asthma and COPD. Nose/throat swabs and sputum samples were collected and examined by multiplex polymerase chain reaction for respiratory viruses and cultured for bacteria. The primary outcomes were length of stay (LOS) and readmission to hospital within 60 days. Results: A total of 199 subjects were recruited (96 had asthma and 103 COPD) for 235 events (36 re‐presented). A virus was detected in 79 subjects (40%), bacteria in 41 (21%), and of these, 18 had both. Rhinovirus A was the most frequently isolated virus. A multivariate analysis was performed to control for confounders. It found that detection of a virus, a virus and bacteria, forced expiratory volume in 1 s (FEV1 ) and a diagnosis of COPD were all independent predictors of prolonged LOS, while risk of readmission within 60 days was increased with virus infection alone, virus and bacterial infection, lower FEV1 and current smoking. Conclusions: Virus infection, especially in the presence of chronic bacterial infection, is an important determinant of more severe acute exacerbations in both asthma and COPD, and patients with co‐infections are more likely to be readmitted to hospital following their exacerbation. Abstract : A virus infection with rhinovirus A has been demonstrated to be a likely trigger of acute asthma and COPD. Virus infection, in combination with a chronic bacterial infection, is an important determinant of more severe acute exacerbations and is more likely to result in hospital readmission following severe acute exacerbation.